Great Lakes Pork, Inc. establishing a cross-border pork production company - Phelps, Joel (Kansas State University, 2009)
Establishing a cross border swine production system is the focus of this thesis. There are three basic sections to this project: 1) the business plan information 2) the study of economic principles and the state of the industry, and 3) the implementation of starting the business. First the project develops a basic business plan for Great Lakes Pork, and then uses economic theories to evaluate business opportunities. The project incorporates basic business plan information such as establishing a business philosophy, which includes company goals and objectives. The process involved the creation of specific business entities and the analysis of different corporate structures: Limited Liability Corporation (LLC), Sub S Corporation, and Class C Corporation. Through this process of establishing this cross border swine production company the Partnership and Cooperative business structures are also evaluated and formed. Great Lakes Pork, Inc was incorporated in Michigan as a Sub S corporation. Economies of size and scale are used as the background for developing this business entity. The Cobweb model is used to help understand and explain the existence of a hog cycle and the ramifications this has for Great Lakes Pork, Inc. These economic principles are applied to current North American data to determine an entry point and to predict the best time to enter the swine industry. A study of the United States-Canada exchange rate is required to understand the dynamics of establishing a swine production company that crosses an international border. The study discusses global issues and possible threats that exist to an international corporation. Finally the implementation phase used models to estimate asset values and incorporated tax planning methods to determine the final corporate structure. The implementation phase includes pro-forma financial statements that were used to secure financing. The implementation phase also included renegotiating supplier contracts based on the data learned during the state of the industry analysis to establish a cost of production that could be profitable for the businesses going forward. The end result is an example of the process used to establish a cross border swine production company.
Keywords: Swine; Business plan; Cobweb model; Hog cycle